Public debt in an OLG model with imperfect competition - Peter Skott; Soon Ryoo (University of Massachusetts, Department of Economics, 2011)
Fiscal policy is needed to avoid dynamic inefficiency and maintain full employment in a modified Diamond OLG model with imperfect competition. A distributionally neutral tax scheme can maintain full employment in the face of variations in household confidence. No variations in taxes will be needed if households correctly anticipate future taxes: the tax policy functions as an insurance scheme.
Keywords: E62; E22; 330; public debt; Keynesian OLG model; dynamic efficiency; confidence